Efektivitas Penanganan Korupsi oleh Pemerintahan Susilo Bambang Yudoyono - Said Fadhil (Jurnal Borneo Administrator, 2007)
Corruption has damaged the condition of a nation. The success of combating corruption in Indonesia depends on the effectiveness of President's Yudoyono Administration's prevention and prosecution. This study intents to analyze the level of effectiveness of Yudoyono's handling of corruption. After analyze the two variables, it was concluded that the efforts to handle corruption by Yudoyono's administration is sufficiently effective and increased performance to handling corruption.  Keywords: Corruption, Effectiveness, Policy